Maternal Knowledge and Practices towards Sanitation and Their Relationships with Occurrence of Diarrhoea in Children - Shriya Ankit Seksaria; Mini K Sheth (Intelektual Pustaka Media Utama, 2014)
Diarrhoea, a major contributor of childhood morbidity and mortality is mostly caused by poor hygiene and sanitation. Literature reveal that hygiene practices at household levels greatly affects the occurrence of diarrhoea among children. A cross sectional study was conducted to determine association between hygiene knowledge and practices of mothers with occurrence of diarrhoea in young children below 3 years in the tribal villages of Gujarat. Structured questionnaire was used to elicit information on personal hygiene (PH), food Hygiene (FH), and environmental Hygiene (EH) practices of 536 mothers with children between 6-36 months of age. Past one month diarrhoeal episodes were recorded using the recall method. The mean percent scores for FH, PH and EH practices were 77%, 88% and 80% respectively. Almost 35% children suffered from diarrhoea in the past one month of which 10 were admitted to the hospital. Diarrhoeal incidences were associated with FH and EH practices (p<0.001) and not with PH practices. Improvement in the environmental and personal hygiene practices of the mothers can contribute largely in reducing the prevalence of diarrhoea among children in Chikhli taluka of Gujarat.